Lipid-Lowering Bioactivity of Microalga Nitzschia laevis Extract Containing Fucoxanthin in Murine Model and Carcinomic Hepatocytes - Bingbing Guo; Yonghui Zhou; Bin Liu; Yongjin He; Feng Chen; Ka-Wing Cheng (MDPI AG, 2021)
Non-alcoholic fatty liver disease (NAFLD), characterized by hepatic steatosis, is one of the most common liver diseases worldwide. So far, no definitive medical treatment has been established to treat NAFLD except for lifestyle medication. Nitzschia laevis extract (NLE), a microalgal extract rich in fucoxanthin, has been previously demonstrated to reduce bodyweight in high-fat-diet (HFD) C57BL/6J mice, indicating potential for prevention of NAFLD. In the present study, we investigated the lipid-lowering effects of NLE in HFD-induced steatosis murine model and palmitate-treated HepG2 cells. The results showed that NLE significantly lowered inguinal fat and attenuated hepatic steatosis in C57BL/6J mice. Especially, NLE significantly prevented lipid accumulation in HepG2 cells. This was probably due to its capability to enhance hepatic mitochondrial function as evidenced by the increased oxygen consumption rate (OCR) and mitochondrial membrane potential (MMP), and repress fatty acid synthesis through phosphorylation of acetyl-CoA carboxylase (ACC). Moreover, fucoxanthin was identified to be responsible for the lipid-lowering effect of NLE. Taken together, NLE or other microalgal fucoxanthin-rich products are promising natural products that may help prevent against NAFLD.